Teaching geography and the use of iconographic resources in the construction of significant learning - Barbosa, Gustavo Gomes; Carmo, Thiago Breno de Medeiros (Revista Ensino de Geografia (Recife), 2020)
The purpose of this work is to promote reflection on how recognition takes place, at school, of the relations between Man and the Environment and their influences on the production of new landscapes, that is, through analysis in works artistic works, authored by the modernist painter Tarsila do Amaral. It is also highlighted that the importance of this work is encompassed in the applicability of important researches that demonstrate the potential that can be developed among students, with the use of artistic expressions through methodological applications. Thus, we seek to integrate the formation of ideas and geographical concepts based on the national artistic identity, and as a consequence of this, to inquire about the possibilities and perspectives of what concerns: the formations, meanings and reframings of knowledge and their disciplinary pluralities. The Geography classroom of a 6th grade class of basic education, located in the city of Paulista-PE, was used as a research field, where: diagnoses, reflections and conceptualizations, added the students and teachers expectations for the meaning and expression of the results and insights proposed here